2000
DOI: 10.2190/vltu-ccxf-nfyl-277h
|View full text |Cite
|
Sign up to set email alerts
|

Language Learner Strategies with Technology

Abstract: This study examines use of learning strategies by experienced adult learners of foreign languages. The goal was to determine how these exemplary language learners engage a multimedia environment, what strategies they employ, and how insights on strategy use can be useful for learners and teachers. 285 Ó 2000, Baywood Publishing Co., Inc. LANGUAGE LEARNER STRATEGIES / 287 288 / ULITSKY Figure 1.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 17 publications
0
13
0
Order By: Relevance
“…Several researchers have pointed out, for example, that students coming from traditional language education backgrounds have expectations about what a language class "should" be and may have difficulty adapting to a computer-assisted format (e.g., Dziombak, 1990;Oliva & Pollastrini, 1995). Blyth (1999) and Ulitsky (2000) suggested that the learning context and the background of the students must be taken into consideration when implementing new approaches in software design and learning activities. Furthermore, Lee (1998) pointed out that classrooms based solely on computer-assisted instruction may also limit student participation.…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have pointed out, for example, that students coming from traditional language education backgrounds have expectations about what a language class "should" be and may have difficulty adapting to a computer-assisted format (e.g., Dziombak, 1990;Oliva & Pollastrini, 1995). Blyth (1999) and Ulitsky (2000) suggested that the learning context and the background of the students must be taken into consideration when implementing new approaches in software design and learning activities. Furthermore, Lee (1998) pointed out that classrooms based solely on computer-assisted instruction may also limit student participation.…”
Section: Resultsmentioning
confidence: 99%
“…There are several studies that focus on this, such as Blyth (1999), Bradley and Lomicka (2000), Donaldson and Kotter (1999), Kubola (1999), Lee (1997), Osuna and Meskill (1998), Ulitsky(2000), Ushida (2005),and Wong et al (2013).Very few recent studies pay attention to teachers' perception on the issue, one of them being Russell et al (2003) and more recently Kalaja and Ferreira Barcelos (2012). Our study focuses on teachers' use of CALL, however, in our paper we will also consider teachers' attitudes towards technology in language learning.…”
Section: Review Of Literaturementioning
confidence: 99%
“…Two possible solutions to this dilemma present themselves: one focuses on learners and the other on the instructional design of the learning materials they use. Hubbard (2004) and Chun and Payne (2004) stated that since students can, naively or deliberately, circumvent software design features, they need training on how to make the best use of the features built into programs (see also Ulitsky, 2000). Hoven (1999, p. 158) captures this notion succinctly in the expression that learners need ''guidance and guided practice'' to become autonomous learners, that is, students need not only to be taught how to take advantage of software features, they also need practice, as Hubbard has suggested in a cyclic approach of training !…”
Section: Learner Autonomymentioning
confidence: 99%